The mechanism of rotational and non-rotational shoulder affecting the microstructure and mechanical properties of Al-Mg-Si alloy friction stir welded joint - Hua Ji; Yunlai Deng; Hongyong Xu; Sen Lin; Wenquan Wang; Honggang Dong (Materials & Design, 2020)
Butt joining of Al-Mg-Si alloys with 6.0 mm in thickness was made with conventional rotational shoulder friction stir welding (RSFSW) and non-rotational shoulder friction stir welding (NRS-FSW) process, respectively, and the resultant mechanism of different shoulders affecting the microstructure and mechanical properties of joint was discussed. A new zone named “triangle zone” (TZ) in the RSFSWed joint was first clearly defined, while the shoulder and pin affected zone (SPAZ) did not exist in the NRS-FSWed joint. The distribution of average grain sizes in each zone of the joints (“M” shape) and the changes in the proportion of high angle grain boundaries (HAGBs) (“W” shape) are unified with the typical “W” shape distribution of microhardness in the joints. Compared to rotational shoulder, the non-rotational shoulder significantly reduced the width of softened area. In particular, the microstructure of the joints by NRS-FSW with triple facets on the pin surface is finer, denser and more homogeneous. The tensile strength coefficient of the joint welded by NRS-FSW and NRS-FSW with the pin of triple facets increased by 2.3% and 11.6%, respectively, compared to the joint welded by RSFSW. Accordingly, the fatigue performances increased by 1.72 times and 3.19 times, respectively.